Identification and Evolution Analysis of Literature Themes in Literature Resource Guarantee System in China - Tian Xuran (LIS Press, 2021)
[Purpose/significance] By analyzing the path of thematic evolution of literature resource guarantee system in China, this paper provides references for reconstructing literature resource guarantee system in China.[Method/process]This paper used LDA model to cluster the collected documents. Firstly, it used the time period as the basis of division, drew the co-occurrence network of topic words, and explored the interactions between topics. Then the paper determined the evolution path within each subject by similarity calculation and showed it in the form of visualization by drawing Sankey diagram. [Result/conclusion] The study finds that all the relevant themes of literature resource guarantee system in China have basically appeared around 2000. The topic mainly includes two categories of resources and institutions, which are greatly influenced by computer technology and national policy. The corresponding countermeasures and suggestions are given for these two categories of topics.